Ultrafast non-radiative dynamics of atomically thin MoSe2. Issue 1 (December 2017) - Lin, Ming-Fu; Kochat, Vidya; Krishnamoorthy, Aravind; Bassman, Lindsay; Weninger, Clemens; Zheng, Qiang; Zhang, Xiang; Apte, Amey; Tiwary, Chandra; Shen, Xiaozhe; Li, Renkai; Kalia, Rajiv; et al.
Abstract Photo-induced non-radiative energy dissipation is a potential pathway to induce structural-phase transitions in two-dimensional materials. For advancing this field, a quantitative understanding of real-time atomic motion and lattice temperature is required. However, this understanding has been incomplete due to a lack of suitable experimental techniques. Here, we use ultrafast electron diffraction to directly probe the subpicosecond conversion of photoenergy to lattice vibrations in a model bilayered semiconductor, molybdenum diselenide. We find that when creating a high charge carrier density, the energy is efficiently transferred to the lattice within one picosecond. First-principles nonadiabatic quantum molecular dynamics simulations reproduce the observed ultrafast increase in lattice temperature and the corresponding conversion of photoenergy to lattice vibrations. Nonadiabatic quantum simulations further suggest that a softening of vibrational modes in the excited state is involved in efficient and rapid energy transfer between the electronic system and the lattice. Knowledge of the energy transfer pathways in transition metal dichalcogenides is essential to design efficient optoelectronic devices. Here, the authors use megaelectronvolt ultrafast electron diffraction to unveil the sub-picosecond lattice dynamics in MoSe2 following photoexcitation of charge carriers